A Systematic Review of Pediatric Obesity and Family Communication Through the Lens of Addiction Literature - Mogul, Ashley (Mary Ann Liebert, Inc., 2014)
Background: Both treatment of addiction and treatment of pediatric obesity often integrate the family unit. Thus, addiction therapies may provide a model to guide treatment of pediatric obesity, particularly issues of family communication, weight, and weight-related behaviors. The aim of this systematic review is to assess what knowledge in the field of addiction treatment can be translated to pediatric weight management, particularly in relation to family-based approaches and communication. Methods: A systematic review of family communication and food addiction in obese children was conducted using MEDLINE and other databases, including all English-language studies published after 1990 meeting search criteria and related to family factors or family communication, and addiction treatment strategies used in obesity interventions. Results: Three reviews, two survey studies, and two observational studies were included. Most focused on family communication; less-healthy communication patterns and parental restriction were related to maladaptive eating behaviors in children and attrition from weight management programs. A few studies suggested family communication interventions to improve unhealthy eating patterns in children, using therapies common in family treatment of addiction (e.g., motivational interviewing and cognitive behavioral therapy). No studies presented concrete suggestions to aid family communication around issues of food and weight management. Potential contributions of addiction therapies are discussed. Conclusions: Though the addictive properties of food have not been fully delineated and obesity is not classified as a disease of addiction, the field of addiction offers many approaches that may prove useful in the treatment of obesity.